2011
DOI: 10.1007/s13346-011-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanofibrous scaffold with incorporated protein gradient for directing neurite outgrowth

Abstract: Concentration gradient of diffusible bioactive chemicals assumes many important roles in regulating cellular behavior. Among the many factors influencing functional recovery after nerve injury, such as topographical and biochemical signals, concentration gradients of neurotrophic factors provide chemotactic cues for neurite outgrowth and targeted renervation. In this study, a concentration gradient of nerve growth factor (NGF, 0-250 μg/ml) was incorporated throughout the thickness of poly(ε-caprolactone)-poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…More importantly, our scaffold design allows robust drug/gene encapsulation. Our previous works have shown that electrospinning enabled the incorporation of a wide variety of drugs ranging from proteins to low molecular weight lipophilic drugs and nucleic acids within nanofiber matrices 16 17 18 19 20 21 22 23 24 25 26 . Collagen hydrogel, on the other hand, is well-established in its ability to enable sustained drug/gene delivery 27 28 29 .…”
mentioning
confidence: 99%
“…More importantly, our scaffold design allows robust drug/gene encapsulation. Our previous works have shown that electrospinning enabled the incorporation of a wide variety of drugs ranging from proteins to low molecular weight lipophilic drugs and nucleic acids within nanofiber matrices 16 17 18 19 20 21 22 23 24 25 26 . Collagen hydrogel, on the other hand, is well-established in its ability to enable sustained drug/gene delivery 27 28 29 .…”
mentioning
confidence: 99%
“…Moreover, we have previously employed similar electrospun substrates for the delivery of proteins and low molecular weight drugs [27][28][29]. Thus, this microfiber substrate could be a versatile functional drug/gene screening platform for OLs.…”
Section: Discussionmentioning
confidence: 99%
“…designed poly(ε‐caprolactone)‐poly(ethylene glycol) coaxial electrospun nanofibrous scaffolds in which a gradient of NGF was incorporated (0–250 µg mL −1 ). [ 67 ] When cells were in contact with scaffolds containing the gradient, a higher percentage of cells bearing neurite outgrowth was observed, when compared with scaffolds containing a fixed NGF concentration. [ 67 ] Also, Chang et al.…”
Section: Biomedical and Pharmaceutical Applications Of Cgmsmentioning
confidence: 99%
“…[ 67 ] When cells were in contact with scaffolds containing the gradient, a higher percentage of cells bearing neurite outgrowth was observed, when compared with scaffolds containing a fixed NGF concentration. [ 67 ] Also, Chang et al. designed a gelatin‐based nerve conduit, mimicking the architecture of a nerve, with spatial gradients of neurotrophic factors (NGF and brain‐derived neurotrophic factor (BDNF)) either encapsulated in gelatin nanoparticles (for controlled release) or directly incorporated in the gelatin‐scaffold.…”
Section: Biomedical and Pharmaceutical Applications Of Cgmsmentioning
confidence: 99%